2020
DOI: 10.2533/chimia.2020.814
|View full text |Cite
|
Sign up to set email alerts
|

TOP-N53: A Clinical Drug Candidate for the Treatment of Non-healing Wounds

Abstract: Chronic non-healing wounds impose a huge burden on patients and health care providers. In spite of improvements in standards of care there are no effective and safe treatments that promote new tissue formation and wound closure in ailments such as diabetic foot ulcer, pressure ulcer, venous leg ulcer or digital ulcer in systemic sclerosis. Endothelial dysfunction, which associates with impaired endogenous nitric oxide formation is assumed to be a main disease mechanism in chronic, non-healing wounds in diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…It is hoped that recent systematic reviews on topical nitrates [57,58] ] reported a preclinical study investigating the formulation of a novel nifedipine cream stable to ultraviolet light. Topical PDE5 inhibitors are also being researched [63,64] and topical econazole nitrate, an antagonist of Transient Receptor Potential Melastatin 8 has been studied in vitro [61,66 & ]. These are all important steps forward towards long-awaited clinical trials of topical treatments.…”
Section: Topical Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is hoped that recent systematic reviews on topical nitrates [57,58] ] reported a preclinical study investigating the formulation of a novel nifedipine cream stable to ultraviolet light. Topical PDE5 inhibitors are also being researched [63,64] and topical econazole nitrate, an antagonist of Transient Receptor Potential Melastatin 8 has been studied in vitro [61,66 & ]. These are all important steps forward towards long-awaited clinical trials of topical treatments.…”
Section: Topical Therapiesmentioning
confidence: 99%
“…Although the use of topical glyceryl trinitrate for Raynaud's phenomenon was suggested as far back as 1951 [56], progress with topical therapies has been very slow. It is hoped that recent systematic reviews on topical nitrates [57,58] herald a wave of new interest, with several publications on topical therapies over the last 3 years [59–61,62 ▪ ,63–65,66 ▪ ]. Wasan et al [62 ▪ ] reported a preclinical study investigating the formulation of a novel nifedipine cream stable to ultraviolet light.…”
Section: Treatmentmentioning
confidence: 99%
“…When formulated in a liquid hydrogel, this compound can be used for topical application on wounds. Hydrogel formulations as presented in this study will be particularly suitable for wounds that allow a daily treatment, such as digital ulcers that result from poor blood flow due to vasoconstriction in systemic sclerosis patients [36]. Therefore, the results presented here encourage further translational research, including the development of delivery systems that allow application of TOP-N53 in a time-controlled manner and appropriate dose for improved treatment of chronic, non-healing skin wounds.…”
Section: Discussionmentioning
confidence: 80%
“…Sildenafil is a phosphodiesterase type 5 (PED5) inhibitor, and the compound TOP‐N53 (Figure 3) was obtained by introducing NO donor based on its PED5 inhibitor structure, which improves intracellular cGMP levels through NO release, restores microcirculation in wound tissues, and promotes angiogenesis. Currently, TOP‐N53 is used for the therapy of impaired wound healing caused by diabetes and is in phase I clinical trials (Ben‐Yehuda Greenwald et al, 2021; Naef et al, 2020). In addition, the NO‐aspirin hybrid drug NCX 4016 (Figure 3) significantly reduced endothelial cell apoptosis, promoted reparative vascular angiogenesis, and attenuated the effects of secondary arterial occlusion more effectively compared to aspirin alone (Emanueli et al, 2004).…”
Section: Therapeutic Strategies For Reduced Vascular Angiogenesis Dur...mentioning
confidence: 99%